Reclaiming Agrarian Justice: The Reformative Potential of Islamic Land Law through Maqāṣid al-Sharia - Ahmad Syafi’i SJ; Putri Ayu, Diyan; Anuar Nordin, Shah Rul; Abubakar , Fatum; Bin Borham, Abd Shakor (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2025)
Research Objective: This study explores the reformative potential of Islamic agrarian law, focusing on land tenure institutions such as ḥimā (protected area) and iqṭā’ (fief). It challenges the notion that Islamic law is fixed, investigating how its historical evolution can inform responses to modern socio-ecological challenges. Research Method: A qualitative historical-legal method is employed, drawing from classical jurisprudence, historical records, and contemporary scholarship across various Islamic legal schools. The analysis is conducted through the lens of Maqāṣid al-Sharia, emphasizing normative objectives. Results: The study uncovers that Islamic agrarian law is inherently dynamic. Historical data demonstrate that institutions like ḥimā and iqṭā’ have undergone reinterpretation and transformation to accommodate evolving governance, environmental needs, and societal demands. Findings and Implications: Key findings show that Islamic land laws emphasize justice, sustainability, and public welfare. Institutions have been used to promote ecological conservation and equitable resource distribution. These insights support the revitalization of Islamic land frameworks for inclusive and ethical land reform in the modern Muslim context. Conclusion: Islamic legal tradition contains inherent pluralism and flexibility, capable of integrating local customs and socio-economic realities. This adaptive capacity enhances its relevance for contemporary agrarian issues. Contribution: The study contributes a conceptual and normative foundation for reimagining Islamic land tenure models within modern governance, offering pathways to sustainable and just agrarian reform. Limitations and Suggestions: As a primarily conceptual and historical inquiry, this research encourages future empirical studies to test the implementation and policy impact of these legal principles in present-day land governance systems.